Post-2020 Global Biodiversity Strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CCAFS' contributions to the negotiation of the 'Post-2020 Global Biodiversity Strategy' being developed for adoption by the Conference of the Parties to the Convention on Biological Diversity